ANALYSIS OF THE EFFECT OF 3DVAR AND ENSRF DIRECT ASSIMILATION OF RADAR DATA ON THE FORECAST OF A HEAVY RAINFALL EVENT - 刘寅 何光鑫 刘佳伟 赵虹 燕成玉 (Journal of Tropical Meteorology, 2016)
The present study designs experiments on the direct assimilation of radial velocity and refiectivity data collected by an S-band Doppler weather radar （CINRAD WSR-98D） at the Hefei Station and the reanalysis data produced by the United States National Centers for Environmental Prediction using the Weather Research and Forecasting （WRF） model, the WRF model with a three-dimensional variational （3DVAR） data assimilation system and the WRF model with an ensemble square root filter （EnSRF） data assimilation system. In addition, the present study analyzes a Meiyu front heavy rainfall process that occurred in the Yangtze-Huaihe River Basin from July 4 to July 5, 2003, through numerical simulation. The results show the following. （1） The assimilation of the radar radial velocity data can increase the perturbations in the low-altitude atmosphere over the heavy rainfall region, enhance the convective activities and reduce excessive simulated precipitation. （2） The 3DVAR assimilation method significantly adjusts the horizontal wind field. The assimilation of the reflectivity data improves the microphysical quantities and dynamic fields in the model. In addition, the assimilation of the radial velocity and reflectivity data can better adjust the wind fields and improve the intensity and location of the simulated radar echo bands. （3） The EnSRF assimilation method can assimilate more small-scale wind field information into the model. The assimilation of the refiectivity data alone can relatively accurately forecast the rainfall centers. In addition, the assimilation of the radial velocity and reflectivity data can improve the location of the simulated radar echo bands. （4） The use of the 3DVAR and EnSRF assimilation methods to assimilate the radar radial velocity and refiectivity data can improve the forecast of precipitation, rain-band areal coverage and the center location and intensity of precipitation.